Embarking on a Researcher Career: Involvement in Writing for Publication - Amalia Nurhasanah; Aryawira Pratama; Mayang Sastra Sumardi; Mahmudah, Khotimah; Wahyuni Fitria; Edi Rozal (UNIB Press, 2023)
Personal Branding is a step taken by a lecturer, one of which is publishing articles in accredited journals. Academic writing is intended to contribute to the field of education both practically and theoretically. This scientific research focuses on descriptive analysis of lecturers' voices about the struggle in achieving a publication target. The author uses a qualitative method with a phenomenological design and semi-structured interviews to obtain data from selected senior lecturers at certain public institutions. In general, the findings of this research are categorized into six points. Of the two sub-themes, the research results tend to lead to positive and negative attitudes in English-language publications. Furthermore, the discursive challenge shows that Participants have difficulty writing with regard to word choice, grammar, and vocabulary bank, while the non-discursive challenge shows that Participants have difficulty processing their soft skills such as time management in writing and financial management in publications. In terms of psychology, the lecturers' internal motivation in writing is the target for achieving a higher career. The more they write, the more performance points they get so they can reach a certain career level. Meanwhile, external motivation is in the form of government regulations and legal institutions that require an educator in higher education to carry out scientific activities such as research and reports in the form of published scientific articles. The implications of this research are expecting support from the institution where they work and the writer's family to understand their obligations as a lecturer.